Can increased education help reduce the political opportunity gap? - Karl-Oskar Lindgren; Sven Oskarsson; Mikael Persson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
It is well documented that voter turnout is lower among persons who grow up in families of low socio-economic status compared to persons from high-status families. This paper examines whether reforms in education can help to reduce the socio-economic gap in voting. We distinguish between reforms of two types that may lead to differences in the exercise of voting; (a) changes in the resources allocated to education between different socio-economic groups (reform effects) and (b) changes in return which relate to the impact of education on turnout in different groups. We use this framework to analyze a reform of the Swedish upper secondary school system in the 1990s. This reform increased the length and amount of social science education on vocational training programs. We find that the reform reduced the gap in voting mainly by means of its stronger influence among individuals from families of low socio-economic status.
Keywords: H7; I24; 330; Political inequality; political participation; voting; education